PROPER EVENT PLANNING AS A VERITABLE TOOL FOR PROMOTING CULTURAL RELATIVISM (American Journal of Interdisciplinary Research and Development, 2025)
This study examines the relationship between proper event planning and the promotion of cultural relativism, with a focus on the Calabar Carnival in Nigeria. The research explores how well-organized cultural events contribute to fostering intercultural appreciation, preserving indigenous traditions, and promoting social harmony. A mixed-methods approach was employed, combining both qualitative and quantitative data collection and analysis methods. The study reveals that proper event planning significantly promotes cultural relativism in social and cultural events, while mega-events like the Calabar Carnival have a profound influence on intercultural interactions and cultural understanding. The findings highlight the importance of inclusive event planning, cultural sensitivity, and authenticity in promoting cultural appreciation and unity. The study contributes to the existing body of knowledge on event management, cultural relativism, and intercultural interactions, providing valuable insights for event planners, cultural policymakers, and scholars in the field. The research recommends that event planners prioritize cultural authenticity, inclusivity, and sensitivity to promote cultural relativism and unity, and suggests avenues for future research on the long-term effects of mega-events on intercultural relations.